2013
DOI: 10.7717/peerj.137
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status among adolescents in Georgia. A pathfinder study

Abstract: Objectives. The aim of the present pathfinder study was to screen and map the periodontal status of Georgian population in accordance with the guidelines of the World Health Organization for population based surveys.Methods. During 2012, a pathfinder study was conducted to collect this data. For the periodontal portion of the study, 15-year-old school children were examined in the capital city of Tbilisi as well as in two other large cities and 4 smaller villages. All participants were examined by a trained de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
1
19
1
1
Order By: Relevance
“…The current investigation was based on a previous successful experience, conducted by almost the same research team, in the Republic of Georgia.…”
Section: Introductionmentioning
confidence: 99%
“…The current investigation was based on a previous successful experience, conducted by almost the same research team, in the Republic of Georgia.…”
Section: Introductionmentioning
confidence: 99%
“…19 However, taking into consideration our data, the occurrence of shallow pockets was greater than in Greece -0.2% 23 and smaller than in Georgia -35.36%. 22 The proportion of Polish adolescents who reported brushing their teeth twice a day or more often was higher in 2008 than in 2015. In contrast, in England, Wales and Northern Ireland, it increased from 80% in 2003 to 85% in 2013.…”
Section: Discussionmentioning
confidence: 94%
“…The proportion of 15-year-olds with gingival bleeding varied in different countries from 25% to 92%. 5,7,19,[21][22][23] Gingival bleeding evaluated by the application of a periodontal probe around 6 index teeth within 10 years (2003-2013) decreased in England (from 45% to 40%) and Northern Ireland (from 44% to 41%), but increased in Wales (from 37% to 42%). 19 However, taking into consideration our data, the occurrence of shallow pockets was greater than in Greece -0.2% 23 and smaller than in Georgia -35.36%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dental caries, periodontal disease is another oral disease that is concerning at this stage of life. The World Health Organization (WHO) recently reported that most children and adolescents show signs of gingivitis [3], whose prevalence is up to 80% in adolescents [8]. According to the latest Brazilian nationwide oral health survey, more than half of the adolescents aged 15 to 19 years show signs of the disease, such as bleeding (9.7%), calculus (28.6%) and periodontal pockets (10.8%) [9].…”
Section: Introductionmentioning
confidence: 99%